Parent-Led Activity and Nutrition (PLAN) for Healthy Living: Design and Methods - Dalton, William T. (2011)
Child obesity has become an important public heath concern, especially in rural areas. Primary care providers are well positioned to intervene with children and their parents, but encounter many barriers to addressing child overweight and obesity. This paper describes the design and methods of a cluster- randomized controlled trial to evaluate a parent-mediated approach utilizing physician’s brief motivational interviewing and parent group sessions to treat child (ages 5–11 years) overweight and obesity in the primary care setting in Southern Appalachia. Specific aims of this pilot project will be 1) to establish a primary care based and parent-mediated childhood overweight intervention program in the primary care setting, 2) to explore the efficacy of this intervention in promoting healthier weight status and health behaviors of children, 3) to examine the acceptability and feasibility of the approach among parents and primary care providers. If proven to be effective, this approach may be an exportable model to other primary care practices.